If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + w) = 0 (2 * 3 + w * 3) = 0 (6 + 3w) = 0 Solving 6 + 3w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3w = 0 + -6 3w = 0 + -6 Combine like terms: 0 + -6 = -6 3w = -6 Divide each side by '3'. w = -2 Simplifying w = -2
| g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= | | Y=Ax-Fx-C | | z^6-z^3-2=0 | | (12x-8)+3(2x-4)= | | 10x+3=3(2x+1)-x+8 | | -x+3+9x=-2+3x+10 | | -11c=89 | | 5=-3(x+2)-4 | | 6x+3+x=2+2x+21 | | 7x(4+4x)= | | 5x-4=2x+29 | | 5y=9 | | 0=9-5y | | 5x=-6 | | 10x=x+100 | | 6x+5=-2#-9 | | 4x^2-36x=-80 | | 6x+4x=65-3x | | 2+16/2+6=4 | | 3p^2-7p-6=0 | | x^3+2x^2+x-2=0 | | 3x^2-8x*3=0 | | 14m+2-27=m+3 | | -7t=-70 | | x^2-x-38=0 | | 12q=-24 |